Synthesis of porous reduced graphene oxide as metal-free carbon for adsorption and catalytic oxidation of organics in water - Peng, Wenchao; Liu, S.; Sun, Hongqi; Yao, Yunjin; Zhi, L.; Wang, Shaobin (R S C Publications, 2013)
Activation of reduced graphene oxide (RGO) using CO2 to obtain highly porous and metal-free carbonaceous materials for adsorption and catalysis was investigated. A facile one-pot thermal process can simultaneously reduce graphene oxide and produce activated RGO without introducing any solid or aqueous activation agent. This process can significantly increase the specific surface area (SSA) of RGO from 200 to higher than 1200 m2 g-1, and the obtained materials were proven to be highly effective for adsorptive removal of both anionic (phenol) and cationic (methylene blue, MB) organics from water. Moreover, the activated RGO materials exhibited much better activity in effective activation of peroxymonosulfate (PMS) to produce sulfate radicals for oxidative degradation of MB.